A rapid UHPLC-QqQ-MS/MS method for the simultaneous qualitation and quantitation of coumarins, furocoumarins, flavonoids, phenolic acids in pummelo fruits. (30th September 2020) - Zhao, Xi Juan; Guo, Peng Mei; Pang, Wen Hui; Zhang, Yao Hai; Zhao, Qi Yang; Jiao, Bi Ning; Kilmartin, Paul A.
Highlights: A sensitive and rapid analytical method was developed based on UHPLC-QqQ-MS/MS. 47 analytes including 13 groups of isomers could be simultaneously quantitated. Good separation of the 47 analytes was achieved during a 13 min chromatographic run. Furocoumarins and polymethoxylated flavonoids were included in the analytes. The 47 analytes in flavedo, albedo and pulp of pummelo fruits were determined. Abstract: The impact of secondary metabolites on fruit quality, plant growth and human health has led to an increased demand for analytical methods to characterize and quantify these metabolites in recent years. A versatile, sensitive and rapid method based on UHPLC-QqQ-MS/MS was developed for simultaneous qualitation and quantitation of coumarins, furocoumarins, flavonoids and phenolic acids. The chromatographic elution and multiple reaction monitoring mode transitions were optimized to achieve good separation and accurate quantitation of 47 analytes, including 13 groups of isomers, during a single 13 min chromatographic run. This method was validated with good precision and recoveries, wide linear ranges and low limits of detection and quantitation (0.014–1.50 μg L −1 ). The validated method was further applied to quantify the analytes in flavedo, albedo and pulp from two pummelo varieties, C. grandis 'Shatianyu' and C. grandis 'Guanximiyu'. This method combines high sensitivity, good selectivity, and short chromatographic run time.